Liver Disease and Central Nervous System Dysfunction: Linking the Two - A Narrative Review - Maciej Tenderenda; Bartosz Buczkowski; Piotr Oleksy; Agnieszka Klecza; Aleksandra Broniak; Magdalena Reclik; Karol Zieliński; Aarushi Chourasia; Krzysztof Nowakowski; Martyna Chraścina (Kazimierz Wielki University, 2024)
Introduction: Liver dysfunction can significantly impact the central nervous system (CNS), leading to neuropsychiatric complications such as hepatic encephalopathy (HE). HE, a potentially reversible condition, results from the accumulation of toxins, particularly ammonia, which a diseased liver fails to detoxify, affecting brain function. It is commonly associated with chronic liver diseases like cirrhosis but can also occur acutely in cases of fulminant liver failure. Purpose of Research: This review aims to explore the mechanisms linking liver dysfunction to brain impairment in HE and to summarize recent findings on liver disease's effects on CNS dysfunction. Materials and Methods: The review synthesizes findings from 45 studies on HE pathogenesis and treatment, published between 2003 and 2024. These studies, sourced from PubMed and Scopus, focus on mechanisms including ammonia toxicity, neuroinflammation, oxidative stress, and neurotransmitter imbalance. Basic Results: HE pathogenesis is multifactorial, with systemic metabolic disturbances causing complex interactions among neurotoxic ammonia buildup, chronic neuroinflammation, oxidative stress, and neurotransmitter imbalances. Traditional therapies like lactulose and rifaximin primarily target ammonia reduction, while newer treatments, including ammonia scavengers, anti-inflammatory agents, and antioxidants, address specific pathogenic pathways. The gut-liver-brain axis, involving gut microbiota's role in CNS functioning, presents promising avenues for adjunctive treatment. Conclusions: Addressing HE requires a multifaceted approach, including ammonia reduction, inflammation control, and neurotransmitter balance restoration. Traditional therapies remain central to HE management, but emerging treatments and modulation of gut microbiota may enhance outcomes and improve quality of life for patients with liver disease-related brain dysfunction.